Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1088/0957-0233/1/9/020
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance corrections for guard gaps

Abstract: The precise measurement of the dielectric constant requires an accurate knowledge of the guard gap capacitance for the sample permittivity, sample thickness and gap spacing in use. The authors show that the corrections commonly employed are unsatisfactory, and they give numerical calculations for the general case of thick electrodes, and for moderately wide gaps such as are used in thin film technology. A set of recommended practices for good experimental work are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…In 1990, capacitance corrections for guard gaps were summarised by Goad and Wintle [13] and its close-form representation provides a good overview including several valuable corrections and further analytical expansions in order to avoid implicit calculations. Furthermore, in [13], it was concluded that the fringing parameter is only minor affected by electrode thickness. Moreover, computational calculations are presented considering different permittivities for the test sample and the gap of the guard ring setup and recommendations focusing on capacitance measurements are provided.…”
Section: Field Distribution In Guarded Electrode Setupsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1990, capacitance corrections for guard gaps were summarised by Goad and Wintle [13] and its close-form representation provides a good overview including several valuable corrections and further analytical expansions in order to avoid implicit calculations. Furthermore, in [13], it was concluded that the fringing parameter is only minor affected by electrode thickness. Moreover, computational calculations are presented considering different permittivities for the test sample and the gap of the guard ring setup and recommendations focusing on capacitance measurements are provided.…”
Section: Field Distribution In Guarded Electrode Setupsmentioning
confidence: 99%
“…The work of Endicott [12] in 1976 is fostering the results presented above, whereas especially for implicit equations, expansions are provided in order to allow direct calculations. In 1990, capacitance corrections for guard gaps were summarised by Goad and Wintle [13] and its close‐form representation provides a good overview including several valuable corrections and further analytical expansions in order to avoid implicit calculations. Furthermore, in [13], it was concluded that the fringing parameter is only minor affected by electrode thickness.…”
Section: Conductivity Measurement: Setups Fringing Effects and Inmentioning
confidence: 99%
“…This effective area of the measuring electrode is actually larger than its geometrical surface due to the edge fringing effect. The effective radius of the measuring electrode has been well investigated and several correction expressions have been obtained [3][4][5][6][7][8][9]. Thomson used conformal transformation to obtain the field distribution in a guarded electrode system [3].…”
Section: Introductionmentioning
confidence: 99%
“…Amey calculated an effective radius under the condition that the permittivity of the sample is much higher than that of air [6]. Goad and Wintle reviewed the equations for the guard gap correction and evaluated the validity of these equations in capacitance measurement [7]. Lisowski and co-workers have derived correction expressions when the sample's permittivity is not high and proposed advice to IEC 60093 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers were struggling with accuracy in capacitance determinations for more than a century [4][5][6]. In general, there are two suggested methods to limit this effect, one is to use a guard ring which confines the effective measured area [7]; another one is to compensate the measured capacitance with a correction factor by either analytical calculations or numerical estimations [6,8]. Dielectric response, in application of high voltage engineering, is often measured from a high impedance current shunt [3] and resulting in non-negligible voltages generated at the measuring electrode.…”
mentioning
confidence: 99%